Exploring the reception of the tele-based music program in people with parkinson’s disease during the period of the movement control order due to the covid-19 pandemic - Ang, Mei Foong; Selvarajah, Indra (Human Resource Management Academic Research Society, 2021)
One of the consequences of the Covid-19 pandemic was the country’s lockdown with the new normal “social-distancing” being mandated. This might have worsened the management of some chronic diseases such as Parkinson’s Disease (PD). PD is a chronic neurodegenerative disease in which the symptoms of the disease worsen over time. Apart from the prominent motor problems, studies also noted that the quality of life (QoL) of the People with Parkinson’s Disease (PwP) deteriorates significantly with increasing disease severity. The impairment in the QoL often causes PwP to social withdrawal and social isolation, leading to higher possibilities for PwP to develop neuropsychiatric disorders such as anxiety and depression, as well as causing caregivers’ distress. A tele-based music program was designed for the PwP aiming to encourage social engagement and to instil positive living. This paper reports the preliminary findings of the reception of a trial tele-based music program on psychosocial wellbeing in people with PwP.